Capital social e qualidade de vida relacionada a saúde bucal entre adultos e idosos brasileiros - Camargo, Fernanda Dalmolin de (2021)
The Brazilian population aging is growing, inverting the age pyramid and constituting a social process that is not only the effects of demographic variables, but also causing social and economic changes that create challenges in the aging process associated with a good quality of life that it can also be influenced by social capital and its structural and cognitive dimensions. Because of this, the aim of this study was to verify the association between the dimensions of structural and cognitive social capital with the quality of life related to oral health among Brazilian adults and elderly people. This is a cross-sectional study with data from 9.412 individual aged 50 or over residing in Brazil and participating in the Longitudinal Study of Health of Elderly Brazilians (ELSI BRASIL) which took place in 2015. The outcome used was oral health-related quality of life investigated using the Oral Impacts on Daily Performance (OIDP) instrument. The main predictor was social capital, considering its structural and cognitive dimensions. To adjust the models, independent demographic, socioeconomic, behavioral and psychosocial variableswereused. Poisson regression models were adjusted considering the complex sample using the svy command of the statistical program Stata 14.0 to generate the prevalence ratios. The research was approved by the Research Ethics Committee of the Oswaldo Cruz Foundation and the processis registered in Plataforma Brasil. As a result, individuals who reported lack of confidence in the neighborhood and not having friends had 20% (PR: 1.20; 95% CI: 1.12-1.29) and 12% (PR: 1.12; 95% CI: 1.03-1.21), respectively, higher prevalence of having worse HRQoL, relative to those who trust the neighborhood and reported having friends. We suggest that the cognitive dimension of social capital maybe associated with quality of life related to oral health. This study intends to contribute to the understanding of the relationships between social capital, main lyre garding the structural and cognitive dimensions, and the quality of life related to oral health. It can be a potential subsidy for the formulation of public policies that have a positive impact on the quality of life and oral health of the Brazilian adult and elderly population.